2022
DOI: 10.1007/s00737-022-01257-1
|View full text |Cite
|
Sign up to set email alerts
|

The social predictors of paternal antenatal mental health and their associations with maternal mental health in the Queensland Family Cohort prospective study

Abstract: Antenatal depression (AND) affects 1 in 10 fathers, potentially negatively impacting maternal mental health and well-being during and after the transition to parenthood. However, few studies have assessed the social predictors of paternal AND or their possible associations with maternal mental health. We analysed data from 180 couples participating in the Queensland Family Cohort longitudinal study. Both parents completed surveys measuring mental health, relationship quality, social support, and sleep quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…On one hand, early postpartum surveys evaluating depressive symptoms found that stress and partner’s depressive symptoms were predictive of both mother and father depressive symptoms [ 9 ]; on the other hand, longitudinal surveys of partners found fathers’ prenatal depression predicted worsening maternal depression, but the opposite relationship was not found for paternal depression [ 32 ]. Complicating the relationship even further, a recent longitudinal cohort study of couples found no relationship between maternal and paternal depression, but only found relationships among social support and depression, anxiety, and stress for both parents [ 33 ]. A recent meta-analysis estimated concurrent perinatal depression in mothers and fathers at up to 3.18% [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, early postpartum surveys evaluating depressive symptoms found that stress and partner’s depressive symptoms were predictive of both mother and father depressive symptoms [ 9 ]; on the other hand, longitudinal surveys of partners found fathers’ prenatal depression predicted worsening maternal depression, but the opposite relationship was not found for paternal depression [ 32 ]. Complicating the relationship even further, a recent longitudinal cohort study of couples found no relationship between maternal and paternal depression, but only found relationships among social support and depression, anxiety, and stress for both parents [ 33 ]. A recent meta-analysis estimated concurrent perinatal depression in mothers and fathers at up to 3.18% [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that a lack of support from a spouse during this big life change is a significant risk factor for depression 33,34 . However, the quality of connection, rather than just being in one, has been emphasized as a protective factor in some research 35 . An individual's susceptibility to the depressive effects of stress depends on their unique set of resources and coping strategies.…”
Section: Risk Factors For Mental Health Issues During Pregnancymentioning
confidence: 99%